Chemical Composition, In Vivo, and In Silico Molecular Docking Studies of the Effect of Syzygium aromaticum (Clove) Essential Oil on Ochratoxin A-Induced Acute Neurotoxicity - Mostapha Brahmi; Djallal Eddine H. Adli; Imane Kaoudj; Faisal K. Alkholifi; Wafaa Arabi; Soumia Sohbi; Kaddour Ziani; Khaled Kahloula; Miloud Slimani; Sherouk Hussein Sweilam (Plants)
The aim of our research was to understand the impact of ochratoxin A (OTA) exposure on various physiological and behavioral aspects in adult Wistar rats, and to evaluate the efficacy of a Syzygium aromaticum essential oil (EOC) treatment in restoring the damage caused by this toxin. The essential oils were extracted by hydrodistillation, a yield of 12.70% was obtained for EOC, and the GC-MS characterization of this essential oil revealed that its principal major components are eugenol (80.95%), eugenyl acetate (10.48%), β-caryophyllene (7.21%), and α-humulene (0.87%). Acute OTA intoxication was induced by an intraperitoneal (IP) injection of 289 µg/kg/b.w. every 48 h for 12 doses, resulting in significant reductions in the body and brain weights of exposed rats when compared with controls. The neurobehavioral analysis using several behavioral testing techniques, such as the forced swimming, the dark/light test, the Morris water maze, and the open field test, clearly revealed that OTA exposure causes neurobehavioral disorders, including decreased locomotor activity, a reduced willingness to explore the environment, reflecting a state of stress, anxiety and depression, as well as impaired memory and learning. In addition, OTA intoxication has been associated with metabolic disturbances such as hyperglycemia and hypercortisolemia. However, treatment with EOC mitigated these adverse effects by improving body and brain weights and restoring neurobehavioral function. The in silico analysis revealed significant affinities between clove oils and two tested esterase enzymes (ACh and BuChE) that were more than or similar to the four neurotransmitters “dopamine, serotonin, norepinephrine, and glutamic acid” and the co-crystallized ligands NAG, MES, and GZ5. These results highlight the therapeutic potential of EOC in combating the toxic effects of OTA and pave the way for future research into the mechanisms of action and therapeutic applications of natural compounds in the prevention and treatment of poison-induced diseases.